Training Teachers in Podillya Region (Second Half of the Nineteenth – Early Twentieth Century): Legal Aspects - Nadiya Balabust (Pedagogical Discourse, 2013)
Based on processed and analyzed legislative sources, documentary and archival material as well as historical and educational literature, periodicals and researches of pre-revolutionary, Soviet and modern domestic and foreign scholars and lawyers, the author of the article highlighted the problem and proved legal principles of teachers training for the educational sector of Podillya region in the second half of the nineteenth – early twentieth century. As the result of this research numerous materials from Khmelnytsky Regional State Archive were studied and became open for scientific community, the nature and content of the imperial policy of the Russian autocracy in the education sector were analyzed and showed that it was aimed at full centralization and unification and training teachers that could prepare citizens loyal to Tsarist regime.